Enhancing the quality of grape fruit using bunch bagging and chitosan coating against biotic factors - Usman, Talat; Ahmad, Zeeshan; Noman, Muhammad; Kasana, M. Imran; Tariq, Sudheer; Khan, Taj Naseeb (Journal of Pure and Applied Agriculture, 2023)
Grape fruit quality is greatly affected by the attack of insect pests, diseases and use of synthetic chemicals and hence reduces the yield. Therefore farmers uses various applications of insecticides and pesticides to reduce yield damage that are costly and somewhat affect the nutritional quality of the fruits. So, using pre harvest bunch bagging will not only protect the fruit from insect pest attacks, fungal diseases but will enhance the quality and firmness of the fruits. In this regard a field study was conducted at Rawat orchard yards, Rawalpindi, Pakistan during 2013. Chinese bunch bagging, muslin cloth bunch bagging, cement bunch bagging, brown paper bunch bagging, 0.5% chitosan, 1.0% chitosan and 1.5% chitosan were used as treatment combinations. Statistical results of the experiment showed that all the treatments were significantly (p ≤ 0.05) different. The maximum average bunch weight (468.64 g), fruit firmness (1.33 kgf), pH of juice (4.82), total soluble solid (17.08 ºBrix), reducing sugars (2.79%), non-reducing sugars (57.62%) and total sugars (63.3%) were from the plot having Chinese bunch bagging. It is concluded from the results that the use of pre harvest bunch bagging material and application of chitosan based sprays improved and enhanced the quality of grape fruit that helped in minimizing the damage caused by biotic factors on grape yield. © 2021 Department of Agricultural Sciences, AIOU